Off-on polyadenylation strategy as a supplemental mechanism for silencing toxic transgene expression during lentiviral vector production. (June 2014) - Bagnis, Claude; Zwojsczyki, Gael; Chiaroni, Jacques; Bailly, Pascal
Many gene therapy strategies rely on lentiviral-mediated transfer and expression of genes coding for toxic proteins. Methods of controlling transgene expression in target cells have been extensively investigated, but comparatively little attention has been given to controlling toxic protein expression in viral vector-producing cells, despite its potential implications for viral production and transduction efficiency. In this work, we tested a new lentiviral vector with a backbone that inhibits transgene mRNA polyadenylation and subsequent transgene expression in vector-producing cells. Transgene mRNA polyadenylation was not affected in transduced cells. In a model using enhanced green fluorescent protein (EGFP) cDNA under the control of the human phosphoglycerate kinase (PGK) promoter, flow cytometry demonstrated that transgene expression was dramatically decreased in 293T cells transfected with this new vector in its plasmid configuration. Viral production was maintained, and expression was fully restored in transduced HuH7 and 293T cells. These results provide the basis for a new strategy to improve the production of lentiviral vectors expressing toxic transgenes.